Energy poverty from a life cycle sustainability assessment perspective - T.D. Gates; M. Hannouf; D. Gebremedhin; T.D. Beyene; G. Assefa; I.D. Gates (Cleaner Environmental Systems)
Energy poverty (EP) and energy security (ES) are complex, multi-dimensional challenges with profound environmental, economic, and social implications that persist in both developed and developing nations. Addressing EP requires a holistic, life-cycle perspective to prevent unintended consequences, consider problem-shifting and sub-optimization, while managing trade-offs for sustainable ES. However, despite numerous proposed solutions, a comprehensive triple-bottom-line framework that integrates a life-cycle perspective remains absent in EP decision-making. Life cycle sustainability assessment (LCSA) offers a powerful methodology for addressing EP by encompassing all sustainability dimensions needed to eradicate it. This study conducts a comprehensive review of EP determinants and establishes a novel mapping between LCSA impact categories and EP drivers. Findings reveal that affordability, accessibility, and emissions are fundamental to EP/ES, with demographics and regional disparities influencing vulnerability. The mapping highlights primary determinants of EP/ES, including fair salary, poverty alleviation, public commitment to sustainability issues, climate change, and land use. To enhance the applicability of the LCSA framework to EP/ES, new categories related to energy and consumption are introduced, such as ‘education provided online’, ‘policy development and implementation’, and ‘subsidization’, which capture critical nuances of EP solutions. Additionally, identified gaps in LCSA methodology offer new insights for mitigating EP, strengthening ES, and refining LCSA itself for broader sustainability applications.